Ochrona prawna pielęgniarki / położnej w razie agresywnych zachowań pacjentów w podmiotach leczniczych = Legal protection of the nurse / midwife in case of aggressive behavior of patients in therapeutic entities - Augustynowicz, Anna; Czerw, Aleksandra; Wrześniewska-Wal, Iwona; Fronczak, Adam (Journal of Education, Health and Sport, 2015)
Augustynowicz Anna, Czerw Aleksandra, Wrześniewska-Wal Iwona, Fronczak Adam. Ochrona prawna pielęgniarki / położnej w razie agresywnych zachowań pacjentów w podmiotach leczniczych = Legal protection of the nurse / midwife in case of aggressive behavior of patients in therapeutic entities. Journal of Education, Health and Sport. 2015;5(3):259-268. ISSN 2391-8306. DOI: 10.5281/zenodo.16425 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%283%29%3A259-268 https://pbn.nauka.gov.pl/works/550410 http://dx.doi.org/10.5281/zenodo.16425 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.01.2014. Revised 27.02.2015. Accepted: 12.03.2015. Ochrona prawna pielęgniarki/położnej w razie agresywnych zachowań pacjentów w podmiotach leczniczych Legal protection of the nurse / midwife in case of aggressive behavior of patients in therapeutic entities Anna Augustynowicz 1, Aleksandra Czerw 2, Iwona Wrześniewska-Wal 3, Adam Fronczak 2 1. Katedra iZakład Zdrowia Publicznego WUM, Szkoła Zdrowia Publicznego CMKP 2. Katedra iZakład Zdrowia Publicznego WUM 3. Szkoła Zdrowia Publicznego CMKP Correspondence to Anna Augustynowicz PhD, Zakład Zdrowia Publicznego, Medical University of Warsaw, ul. Banacha 1a, 02-097 Warszawa, Poland Tel: + 48 22 599 21 80; fax. + 48 22 599 21 80; e-mail: aaugustynowicz@poczta.onet.p Streszczenie W artykule przedstawiono zasady ochrony prawnej przysługujące pielęgniarce i położnej w razie agresywnych zachowań pacjentów. Personel medyczny w razie agresywnych zachowań pacjentów może dochodzić roszczeń zarówno na drodze procesu karnego, jak i cywilnego. Z punktu widzenia ochrony karnej istotne znaczenie ma fakt, iż pielęgniarka i położna podczas i w związku z wykonywaniem czynności polegających na udzielaniu świadczeń zdrowotnych korzysta z ochrony przewidzianej dla funkcjonariuszy publicznych. W przypadku agresji słownej pacjent może ponieść odpowiedzialność karną za znieważenie funkcjonariusza publicznego (art. 226 k.k.), ewentualnie za zniesławienie (art. 212 k.k.). Do grupy tej należy również dodać przestępstwo kierowania gróźb pod adresem pielęgniarki/położnej (art. 190 k.k.). Następstwem agresji fizycznej może być odpowiedzialność za naruszenie nietykalności cielesnej funkcjonariusza publicznego (art. 222 k.k.), czynną napaść (223 k.k.) a także za spowodowanie lekkiego, średniego lub ciężkiego uszczerbku na zdrowiu (art. 156 k.k., art. 157 § 1 k.k.). Poza sankcjami natury karnej, agresywnie zachowujący się pacjent może ponieść odpowiedzialność cywilną z tytułu naruszenia dóbr osobistych. Dobrem osobistym naruszanym działaniami pacjenta będzie cześć. Agresja fizyczna lub słowna powodować może powstanie szkody majątkowej w postaci straty poniesionej w wyniku zdarzenia szkodzącego, a także utraconych korzyści. W tym przypadku pielęgniarce, położnej przysługuje wobec pacjenta roszczenie z art. 415 k.c. Abstract This paper presents the principles of legal protection enjoyed by the nurse and midwife in the case of aggressive behavior of patients. Medical personnel in the event of violent behavior of patients can seek redress through a process of both criminal and civil law. From the point of view of criminal law important is the fact that the nurse and midwife during and in connection with the performance of the loans of health care benefits from the protection provided for public servants. In the case of verbal aggression, the patient may incur criminal liability for insulting a public official (art. 226 of the Penal Code), or for defamation (art. 212 of the Penal Code). To this group should also be added an offense targeting threats against a nurse / midwife (Art. 190 of the Penal Code). The consequence of physical aggression may be responsible for the assault and battery of a public official (art. 222 of the Penal Code), assault (223 of the Penal Code), as well as causing a light, medium or serious bodily injury (art. 156 of the Penal Code, Art. 157 § 1 of the Penal Code). In addition to the sanctions of a criminal nature, behaving aggressively, the patient may incur liability for the infringement of personal rights. The infringed personal good will honor the patient's activities. Physical or verbal aggression may result in the damage of property in the form of loss incurred as a result of detrimental events, as well as lost profits. In this case, the nurse, midwife patient is entitled to claim under Art. 415 of the Civil Code. Słowa kluczowe: pielęgniarka, położna, agresywny pacjent, ochrona prawna. Keywords: nurse, midwife, aggressive patient, legal protection.